Psychological Effects of a 1-Month Meditation Retreat on Experienced Meditators: The Role of Non-attachment - Montero-Marin, Jesus; Puebla-Guedea, Marta; Herrera-Mercadal, Paola; Cebolla, Ausias; Soler, Joaquim; Demarzo, Marcelo; Vazquez, Carmelo; Rodríguez-Bornaetxea, Fernando; García-Campayo, Javier (Frontiers in Psychology, 2016)
Background: There are few studies devoted to assessing the impact of meditation-intensive retreats on the well-being, positive psychology, and personality of experienced meditators. We aimed to assess whether a 1-month Vipassana retreat: (a) would increase mindfulness and well-being; (b) would increase prosocial personality traits; and (c) whether psychological changes would be mediated and/or moderated by non-attachment. Method: A controlled, non-randomized, pre-post-intervention trial was used. The intervention group was a convenience sample (n = 19) of experienced meditators who participated in a 1-month Vipassana meditation retreat. The control group (n = 19) comprised matched experienced meditators who did not take part in the retreat. During the retreat, the mean duration of daily practice was 8–9 h, the diet was vegetarian and silence was compulsory. The Experiences Questionnaire (EQ), Non-attachment Scale (NAS), Positive and Negative Affect Schedule (PANAS), Satisfaction With Life Scale (SWLS), Temperament Character Inventory Revised (TCI-R-67), Five Facets Mindfulness Questionnaire (FFMQ), Self-Other Four Immeasurables (SOFI) and the MINDSENS Composite Index were administered. ANCOVAs and linear regression models were used to assess pre-post changes and mediation/moderation effects. Results: Compared to controls, retreatants showed increases in non-attachment, observing, MINDSENS, positive-affect, balance-affect, and cooperativeness; and decreases in describing, negative-others, reward-dependence and self-directedness. Non-attachment had a mediating role in decentring, acting aware, non-reactivity, negative-affect, balance-affect and self-directedness; and a moderating role in describing and positive others, with both mediating and moderating effects on satisfaction with life. Conclusions: A 1-month Vipassana meditation retreat seems to yield improvements in mindfulness, well-being, and personality, even in experienced meditators. Non-attachment might facilitate psychological improvements of meditation, making it possible to overcome possible ceiling effects ascribed to non-intensive practices.